2014
DOI: 10.1097/bor.0000000000000098
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in systemic juvenile idiopathic arthritis

Abstract: Purpose of review This review summarizes biomarkers in Systemic Juvenile Idiopathic Arthritis (sJIA). Broadly, the markers are classified under protein, cellular, gene expression and genetic markers. We also compare the biomarkers in sJIA to biomarkers in cryopyrin associated periodic syndromes (CAPS). Recent findings Recent publications showing the similarity of clinical response of sJIA and CAPS to anti IL1 therapies prompted a comparison at the biomarker level. Summary sJIA traditionally is classified u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Particularly, SAA is one crucial parameter to detect subclinical inflammation and risk evaluation for the development of AA-amyloidosis [ 87 ]. Additionally, S100A12 and MRP8/MRP14 can be used for the monitoring of inflammation with a good correlation to inflammation and treatment response [ 86 , 88 ]. Other disorders associated with recurrent systemic inflammation, such as immunodeficiencies, infections, autoimmune diseases, and malignancies, need to be excluded.…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…Particularly, SAA is one crucial parameter to detect subclinical inflammation and risk evaluation for the development of AA-amyloidosis [ 87 ]. Additionally, S100A12 and MRP8/MRP14 can be used for the monitoring of inflammation with a good correlation to inflammation and treatment response [ 86 , 88 ]. Other disorders associated with recurrent systemic inflammation, such as immunodeficiencies, infections, autoimmune diseases, and malignancies, need to be excluded.…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…The search for more reliable biomarkers for seronegative arthritis has resulted in several serum proteins that are associated with disease activity in patients with seronegative arthritis: IL-6, IL-17, IL-23, VEGF, and MMP3 in SpA [6, 7, 4043], and IL-6 and IL-18 in JIA [5, 36, 44], amongst others. Although these proteins correlate with certain clinical aspects of seronegative arthritis, a major problem remains the lack of specificity, and results are often inconsistent; moreover, these putative biomarkers still await validation in cohort studies.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a considerable number of studies are exploring the potential of new diagnostic and predictive markers for several forms of seronegative arthritis, including calprotectin (S100A8/A9) [57]. Whereas in RA serum S100A8/A9 has been widely accepted as a powerful serum biomarker to assess disease activity and to predict therapy response [8], its role as a serum biomarker in seronegative arthritis is still under investigation [912].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, around 6.7%–13% of the patients with sJIA experienced a potentially fatal condition, macrophage activation syndrome (MAS), portrayed by persistent fever, pan-cytopenia, liver abnormalities, lymphadenopathy, coagulopathy and neurological involvement 14 , 15 . Overlapping clinical manifestations, mutual hyper-active innate responses as well as common serum and cellular biomarkers of CAPS and sJIA, particularly those with polycyclic and persistent disease course, can sometimes cause confusion for clinicians 3 , 16 . While the advance of molecular genetic testing was believed to provide strong support to the diagnosis, in a large French study covering 821 cases suspicious with CAPS, only 16% of the cases were identified with NLRP3 mutations 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Many shared gene transcripts have been identified in patients with sJIA and CAPS 18 , 19 . Considerable body of works, additionally, have discussed about the gene expression profiling, cellular markers and serum biomarkers among the two diseases 16 . Limited data, however, were available directly comparing the markers between the two.…”
Section: Introductionmentioning
confidence: 99%